Rancang Bangun Alat Pendeteksi Kesegaran Ikan Berbasis Internet Of Things (IoT) - Risky Pratama (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Design and Development of an Internet of Things (IoT)-Based Fish Freshness Detection Device. Guided by Mrs. Henna Nurdiansari, S.T., M.T., M.Sc. and Mrs. Monika Retno Gunarti, S.Si.T., M.Pd. Indonesia has a great potential in fish production, reaching 12 million tons annually, accompanied by an increase in fish consumption. However, significant challenges arise regarding food safety, especially concerning the sale of non-fresh fish and the presence of formalin. As an innovative solution, a fish freshness and formalin detector based on IoT was developed. This device utilizes the TCS3200 sensor to detect color intensity and the HCHO sensor to detect formalin. This research employed the Research and Development (R&D) method to produce an effective detection device. When the LED is green without a buzzer sound and the LCD displays "Fresh Fish" or "Formalin Free," the fish can be confirmed to be fresh and free of formalin. However, if the LED is red, the buzzer turns on, and the LCD displays "Non-Fresh Fish" or "Fish with Formalin," the fish is considered to be below standard or contains formalin. The device categorizes fish condition into three groups: green (fresh), yellow (less fresh), and red (not fresh), reflecting the fluctuating freshness level. When the HCHO sensor reads a value above 0.5 ppm, the fish is considered to contain formalin, while below 0.5 ppm is considered safe and free from formalin. Therefore, this device can be an effective solution in detecting fish freshness and formalin content, ensuring food safety for consumers.